Who buffers income losses after job displacement? The role of alternative income sources, the family, and the state - Eva Hank; Daniel Fackler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Using the SOEP this paper analyses to what extent alternative income sources, reactions within the household context, and redistribution by the state attenuate earnings losses of displaced workers. Applying propensity score matching and FE estimations, we find that income from self-employment slightly reduces the earnings gap, severance payments buffer losses in the short run. At the household level, there is no added worker effect, but taxes and transfers mitigate income losses substantially.
Keywords: D10; I38; J63; J65; 330